Direct evidence for crossover and chromatid interference in meiosis of two plant hybrids (Lolium multiflorum×Festuca pratensis and Allium cepa×A. roylei) - Ferreira, Marco Tulio Mendes; Glombik, Marek; Perničková, Kateřina; Duchoslav, Martin; Scholten, Olga; Karafiátová, Miroslava; Techio, Vania Helena; Doležel, Jaroslav; Lukaszewski, Adam J; Kopecký, David (Journal of experimental botany, 2021)
Crossing over, in addition to its strictly genetic role, also performs a critical mechanical function, by bonding homologues in meiosis. Hence, it is responsible for an orderly reduction of the chromosome number. As such, it is strictly controlled in frequency and distribution. The well-known crossover control is positive crossover interference which reduces the probability of a crossover in the vicinity of an already formed crossover. A poorly studied aspect of the control is chromatid interference. Such analyses are possible in very few organisms as they require observation of all four products of a single meiosis. Here, we provide direct evidence of chromatid interference. Using in situ probing in two interspecific plant hybrids (Lolium multiflorum×Festuca pratensis and Allium cepa×A. roylei) during anaphase I, we demonstrate that the involvement of four chromatids in double crossovers is significantly more frequent than expected (64% versus 25%). We also provide a physical measure of the crossover interference distance, covering ~30-40% of the relative chromosome arm length, and show that the centromere acts as a barrier for crossover interference. The two arms of a chromosome appear to act as independent units in the process of crossing over. Chromatid interference has to be seriously addressed in genetic mapping approaches and further studies.
Keywords: Festuca; Lolium; Crossing Over, Genetic; jílek; meióza; Onions; meiosis; Meiosis; recombination; chromatidy; česneky; Centromere; hybrid; crossing over (genetika); crossover interference; Chromatids; homoeologous chromosome; chromatid interference